IMPLEMENTATION OF COOPERATIVE LEARNING MODEL USING HIDDEN CHART MEDIA TO IMPROVE STUDENT LEARNING OUTCOMES SOCIAL SCIENCES - Zainun R (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by the still low learning outcomes of social studies students at SD Negeri 002 Muara Lembu. The purpose of this study is to improve students' social studies learning outcomes by applying cooperative learning models with the help of hidden chart media. This research is a classroom action research consisting of two cycles, each cycle consisting of planning, implementation, observation and reflection. The results of this study indicate that, in the basic score of students who complete only as many as 9 (45%) while 11 (55%) have not been completed with an average grade of 63.2. In the first cycle, students who completed as many as 13 (65%) while those who did not complete as many as 7 (35%) with an average grade of 73.1. Cycle II, students who completed as many as 18 (90%) and students who did not complete as many as 2 (10%) with an average grade of 84.3. from this result it can be concluded that by applying cooperative learning models assisted by hidden chart media can improve social learning outcomes of students of SD Negeri 002 Muara Lembu.